Identifying shared genetic loci between coronavirus disease 2019 and cardiovascular diseases based on cross-trait meta-analysis - Guo, Hongping; Li, Tong; Wen, Haiyang (Frontiers in Microbiology, 2022)
People with coronavirus disease 2019 (COVID-19) have different mortality or severity, and this clinical outcome is thought to be mainly attributed to comorbid cardiovascular diseases. However, genetic loci jointly influencing COVID-19 and cardiovascular disorders remain largely unknown. Here we conducted a genome-wide cross-trait meta-analysis to identify shared genetic loci between COVID-19 and cardiac traits. Firstly, from eight cardiovascular disorders, we found positive genetic correlations between COVID-19 and coronary artery disease (CAD, Rg=0.4075, P=0.0031), type 2 diabetes (T2D, Rg=0.2320, P=0.0043), obesity (OBE, Rg=0.3451, P=0.0061), as well as hypertension (HTN, Rg=0.233, P=0.0026). Secondly, we identified 10 shared loci between COVID-19 and CAD, 3 loci between COVID-19 and T2D, 5 loci between COVID-19 and OBE, and 21 loci between COVID-19 and HTN, respectively. These shared genetic loci were enriched in signalling pathways and secretion pathways. In addition, Mendelian randomization analysis revealed significant causal effect of COVID-19 on CAD, OBE and HTN. Our results have shown the shared genetic architecture between COVID-19 and CVD, and will help to shed light on the molecular mechanisms underlying the association between COVID-19 and cardiac traits.